GROWTH RATE, NUTRIENT-ENERGY EFFICIENCY, AND PROFILE OF GASTRO-INTESTINAL TARCT OF NEW LOHMANN BROILER CHICKENS FED DIETS CONTAINING TURMERIC MEAL - Dono, N.D. (Indonesian Society of Animal Science in collaboration with Indonesian Ministry of Agriculture and Faculty of Animal Science UGM, 2014)
The aim of this study was to assess the dietary turmeric (Curcuma longa Linn.) meal supplementation and its possible effect on growth rate, nutrient and energy efficiency, and profile of gastro-intestinal tract of New Lohmann broiler chickens. A hundred of male one-day old chicks were randomly plotted in 5 dietary treatments, with 5 replications, and 4 birds per replicate pen. The basal diets were based on maize and soybean meal with protein contents of 23% (starter) - 20% (grower) and energy contents of 3015 kcal/kg (starter) - 3100 kcal/kg (grower). The treatment diets were: basal diet without turmeric meal (TM) supplementation (control; P1), basal diet with 0,5% TM (P2), basal diet with 1,0% TM (P3), basal diet with 1,5% TM (P4), and basal diet with 2,0% TM (P5). On day 35, one bird with body weight close to the median of the group was sampled from all replicate pens to measure the profile of digestive tract. All collected data were than statistically analized using Randomized Complete Block Design. Results showed that dietary supplementation of turmeric meal with the rate of 0,5 to 2,0% did not affect grwoth rate as well as nutrient and energy efficiency of New Lohmann broiler chickens. The dietary treatment did not influence the weight and length of small intestine, as well as the liver and pancreas weight of 5 weeks old broiler chickens.